Mapping of sex work hotspots to guide targeted HIV prevention: Evidence from eight Ukrainian cities - Oksana Kovtun; Olga Cheshun; Oksana Pashchuk; Kostyantyn Dumchev (PLoS ONE, 2026)
Background Ukraine’s HIV epidemic remains concentrated among key populations, with sex workers (SWs) facing overlapping vulnerabilities, including a history of injection drug use. Although overall HIV prevalence has declined, prevention coverage remains below national and global targets. Accurate mapping of sex work hotspots is essential for effective outreach, yet existing data are fragmented and incomplete, especially in privatized and digitally mediated environments. This study aimed to systematically identify and characterize sex work venues across eight Ukrainian cities and assess their coverage by HIV prevention services. Methods In 2021, we conducted a two-stage, multi-informant mapping study across eight Ukrainian cities, interviewing 1,212 secondary and 2,277 primary key informants, including SWs. Hotspots were characterized by type, perceived safety, access modality, operating schedule, and presence of SW subgroups. We used descriptive statistics, exploratory factor analysis, and multivariable mixed-effects regression to identify factors associated with HIV prevention service coverage. Results Of 2,581 identified hotspots, 2,118 (82.1%) were validated as active. Apartments (43.2%), virtual platforms (11.7%), and street-based sites (11.1%) were the most common. Only 13.7% of hotspots were registered in the national HIV service registry, while 34.1% received prevention service delivery and 18.9% were reached by mobile vans. Coverage was highest at street-based and office-type venues and consistently lowest in private, virtual, and pimp-mediated settings. Service coverage was positively associated with 24/7 or daytime operation, higher perceived safety, open access, and the presence of SWs who inject drugs. Conclusions This study provides comprehensive mapping of sex work hotspots in Ukraine, revealing persistent gaps in HIV prevention for less visible and harder-to-reach SWs. Community-led mapping achieved high validation rates (86.8%) and identified substantial unmet needs in digital and concealed hotspots. Routine hotspot mapping, combined with engagement with SW communities, is essential for data-driven, equitable, and adaptive HIV responses in rapidly changing contexts.